Structural Adaptations and Performance of State Corporations in Kenya - Miano, Leah; Kihara, Peter; Maore, Stephen (Journal of Public Policy and Administration, 2025)
Purpose: In order to thrive in the extremely competitive market dynamics of the twenty-first century, state corporations in Kenya must overcome a number of obstacles and become more organized and efficient. The main objective of this study was to establish the influence of structural adaptations on performance of state corporations. Methodology: Anchored on Dynamic Capabilities View of the Firm, the study employed a cross-sectional study design utilising mixed methods such as quantitative, qualitative and Descriptive analysis. One hundred and seventy-seven (177) state corporations were targeted where a total of 122 State Corporations were randomly selected and used in this study. The unit of observation was the Chief Executive Officer of each sampled organization since they are the vision carriers and accounting officers. A standard questionnaire was used to collect quantitative primary data. Findings: The study found that there is a significant and positive influence of structural adaptations on performance of state corporations in Kenya. The findings were supported by the correlation results which showed a positive and significant association between the two variables (r=0.517, p-value=0.000<0.05). This was also supported by the regression results which revealed that structural adaptations had a positive and significant impact on performance (β1 =0.712, p=0.000). Unique Contribution to Theory, Practice and Policy: This study contributes to theory by extending the Dynamic Capabilities View to public sector institutions, demonstrating how structural adaptations influence performance. It informs policy by advocating for decentralization, digitization, and flattened hierarchies to improve service delivery. Practically, it guides state corporations in redesigning internal structures for greater efficiency, responsiveness, and accountability, offering a contextualized framework for structural reform in Kenya's state-owned enterprises.